RANCANG BANGUN MEDIA PEMBELAJARAN INTERAKTIF MATA PELAJARAN DASAR DESAIN GRAFIS BERBASIS ANDROID - Randi Delfo Putra; Titi Sri Wahyuni (Universitas Negeri Padang, 2019)
Learning media is one important factor in achieving learning objectives. Proper learning media can increase student interest in learning so that learning can take place optimally. Basic Graphic Design subjects is one of the subjects for class X vocational IT which consists of design theory and practice. Interactive learning media is needed to support the learning process. The solution offered is an interactive learning media based on Android. The application development method is prototyping. The final project is designed in the form of an android-based interactive learning media application that students can benefit anytime and anywhere. In the application there are several main menus including the kd1, kd2, kd3 menus, application guides, and about applications. With this application it is hoped that it can improve student understanding in learning Basic Graphic Design. Keywords: Android, Media, Design, Interactive